THE INFLUENCE OF PROMOTION AND TRUST ON THE PURCHASE DECISION OF NATURE REPUBLIC BRAND SKINCARE PRODUCTS TOKOPEDIA CONSUMER STUDY IN TANGERANG CITY - Tarto, Tarto; Tovtora S, Feba Dinova Dex; Laras, Isthi Bayu; Ristiyanto, Reza Rafi (Universitas Muhammadiyah Tangerang, 2024)
This study aims to determine the effect of promotion and trust on purchasing decisions as interverning variables partially or simultaneously. The data analysis method used is casual associative using a quantitative approach. This research uses SPSS version 27. The sample of this research is 96 Tokopedia consumers who buy Nature Republic products as respondents. Sampling using purposive sampling technique using a questionnaire instrument to collect data. The research results show that: 1). Partially Promotion (X1) has a positive and significant effect on Purchase Decision tcount 4.030 > ttable 1.661 with a significance value of 0.001 <0.05 then Ho is rejected and Ha is accepted (Y). 2). Partially Trust (X2) has a positive and significant effect on Purchase Decisions tcount 6.717 > ttable 1.661 with a significance value of 0.001 <0.05 then Ho is rejected and Ha is accepted (Y). 3). Simultaneously, it shows that promotion (X1) and trust (X2) have a positive and significant effect on purchasing decisions (Y). Because the Fcount value (120.615) > Ftable value (3.09) and the significance value F (0.000) < error rate (α = 0.05), then H0 is rejected and Ha is accepted.